Development of an application for electronic retrieval of patient and sample information in latin american regions with a high incidence of gallbladder cancer - Guinez-Molinos, Sergio; Gonzalez Diaz, Jaime; Barahona Ponce, Carol; Lorenzo Bermejo, Justo (Journal of Personalized Medicine, 2022)
The European-Latin American Consortium towards Eradication of Preventable Gallbladder Cancer, EULAT Eradicate GBC, is collecting high-quality data and samples in four Latin American countries with high gallbladder cancer incidence (Argentina, Bolivia, Chile, and Peru) to build a unique biorepository integrated into a tailored IT platform, to identify, validate, and functionally characterize new risk biomarkers, and to develop prediction models that integrate epidemiological and genetic-molecular risk factors. We decided to develop an application for electronic data collection to facilitate the retrieval of sociodemographic, clinical, lifestyle, dietary, and sample-related information from 15,000 Latin American study participants. The application EULAT eCollect will facilitate the work of study nurses, reduce time spent by participants, limit the use of paper and ink, minimize costs and errors associated with filling out written forms and subsequent digitisation, and support the monitoring of local recruitment rates and data quality. We describe in this article the design and implementation of the EULAT eCollect application, which started with the specification of functional and non-functional requirements, and ended with the implementation and validation of four separate application modules: Socio-Demographic Interview, Sample Information, Case Report Form, and Food-Frequency Questionnaire. We present both general and technical results, and our experience with the free and open-source software, Open Data Kit (ODK), which may be of interest for future related research projects, especially those on personalised cancer prevention carried out in low- and middle-income regions.